"Kinesis versus logos" en la filosofía de Leonardo Polo (Anuario Filosófico, 2018)
Kinesis versus logos in Leonardo Polo's philosophy. Kinesis and praxis are analogous concepts in Aristotle. Although Leonardo Polo’s philosophy is right in pointing the differences between these concepts, the article demonstrates that beyond their opposition these terms refer to an analogous pros en: energeia. The author explains Leonardo Polo's necessity to point the difference and Aristotle's concern for pointing their similarity.